The role of income and immigration policies in attracting international migrants - Francesc Ortega; Giovanni Peri (Institute for the Study of Labor (IZA), 2012)
This paper makes two contributions to the literature on the determinants of international migration flows. First, we compile a new dataset on annual bilateral migration flows covering 15 OECD destination countries and 120 sending countries for the period 1980-2006. We also collect data on time-varying immigration policies that regulate the entry of immigrants for our destination countries over this period. Second, we extend the empirical model of migration choice across multiple destinations developed by Grogger and Hanson (2011) by allowing for unobserved individual heterogeneity between migrants and non-migrants. Our estimates show that international migration flows are highly responsive to income per capita at destination. This elasticity is twice as high for within-EU migration, reflecting the higher degree of labor mobility within the European Union. We also find that tightening of laws regulating immigrant entry reduce rapidly and significantly their flow.
Keywords: F22; E25; J61; 330; international migration; labor movements; immigration policies; Internationale Wanderung; Internationale Arbeitsmobilität; Migrationspolitik; Sozialprodukt; Schätzung; OECD-Staaten; Welt